A STUDY ON THE WRITING ENGLISH BUSINESS LETTER DIFFICULTIES AT THE FIRST YEAR STUDENTS ACCOUNTING DEPARTMENT OF SMKN 1 BANDAR SEIKIJANG - Dahler Dahler (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2014)
Students at the first year students accounting department of SMKN 1 Bandar Seikijanghad problems in writing English business letter. They were facing difficulties type of Englishbusiness letter. The Purpose of this research was to find out what kind of difficulties in writing theEnglish business letter faced by the first year students accounting department of SMKN 1 BandarSeikijang. The design of this research was survey. Sample of the research was 23 students at thefirst year students accounting department of SMKN 1 Bandar Seikijang. Instrument used wasquestionnaire. The questionnaire was about the students’ difficulties in writing the Englishbusiness letter. The questionnaire was analyzed by using percentage formulation. The result ofanalyzing data that the students’ response toward their difficulties in writing the English businessletter was making up negative response with 71.73%.In conclusion, the students at the first yearstudents accounting department of SMKN 1 Bandar Seikijang had trouble in studying style ofletter in English business letter.